Simultaneously improved electrical properties of crystalline YbAl3 thin films prepared by co-sputtering technique. Issue 28 (20th March 2017) - Li, Ran-Ran; He, Dan-Qi; Mu, Xin; Zhou, Hong-Yu; Wei, Ping; Zhu, Wan-Ting; Nie, Xiao-Lei; Zhao, Wen-Yu; Zhang, Qing-Jie
Abstract : Crystalline and stoichiometric YbAl3 thin films with high electrical conductivity and high power factors were prepared by a co-sputtering technique and subsequent annealing treatment. Abstract : With the growing interest in developing miniaturized thermoelectric devices, there has been a strong demand in preparing thermoelectric thin films with high electrical conductivity and large power factors, hence ensuring the miniaturized devices have large cooling capacity and large output powers. This work demonstrated the preparation of intermetallic YbAl3 thin films through a double-target magnetron co-sputtering technique and a subsequent annealing treatment. It was revealed that the subsequent heat treatment of thin films plays a critical role in achieving crystalline, stoichiometric, and nanostructured YbAl3 thin films. Benefiting from the significantly improved crystallinity and stoichiometry, the optimized YbAl3 thin films exhibit extraordinarily high electrical conductivity reaching 1.7 × 10 6 S m −1 and large power factors around 7.4 mW m −1 K −2 . The figure of merit ZT of the annealed thin films is comparable with that of the bulk materials, showing their potential use in miniaturized thermoelectric devices.